Implementasi Novel Bat Algorithm Untuk Penjadwalan Ekonomis Pembangkit Listrik Termal Dengan Integrasi PLTB - Nur Fitri, Sulistianingsih; Mustafa, Syahrul; Azis, Fatmawati (Fakultas Teknik Universitas Muhammadiyah Parepare (FT-UMPAR), 2024)
Economic dispatch aims to control the variables of the power system so that the power plants can generate maximally based on load demand according to the characteristics of each plant and with cheaper production costs. In this study, economic dispatch is applied to thermal power plants with the integration of Wind Power Plants (PLTB) in Sulselrabar 150kV power system using the Novel Bat Algorithm (NBA) optimization method, considering voltage stability. The generation cost that can be reduced using the NBA method is IDR 12,583,781 per hour compared to the results of the existing system. With the integration of 100% of the PLTB capacity, the NBA method still provides cheaper economic dispatch results. Using the NBA method, the generation cost can be reduced by IDR 29,854,367 compared to the results of the existing system. After the integration of 100% of the PLTB capacity, the power losses obtained are smaller than before the integration of the PLTB. The system bus voltage conditions before and after the integration of the PLTB are also in good condition as they are within the voltage regulation limits set by PLN, which are +5% and -10%